Russian-olive (Elaeagnus angustifolia) Biology and Ecology and its Potential to Invade Northern North American Riparian Ecosystems. (March 2015) - Collette, Liana K. D.; Pither, Jason
Abstract: Russian-olive is a small tree or large multistemmed shrub that was introduced to Canada and the United States from Eurasia in the early 1900s. It was provisioned in large numbers during the last century to prairie farmers as a shelterbelt plant and remains a popular and widely available ornamental. Now invasive within some riparian ecosystems in the western United States, Russian-olive has been declared noxious in the states of Colorado and New Mexico. With traits including high shade tolerance and a symbiotic association with nitrogen-fixing bacteria, Russian-olive has the potential to dominate riparian vegetation and thus radically transform riparian ecosystems. Especially alarming is its capacity to influence nutrient dynamics within aquatic food webs. Our objective is to draw attention to Russian-olive as a potential threat to riparian ecosystems within Canada, especially in the southwest, where invasion is becoming commonplace. We review what is known about its biology and about the threats it poses to native organisms and ecosystems, and we summarize management and control efforts that are currently underway. We conclude by proposing a research agenda aimed at clarifying whether and how Russian-olive poses a threat to riparian ecosystems within western Canada.